Socially responsible investing: does the environmental pillar of firms´ ESG factors provide information for investors- portfolio returns? Evidence from Europe - Bauer, Dominik Christopher (2021)
In this paper, the influence of the environmental pillar of companies’ ESG scoring on investors’ portfolio returns is analyzed. Based on these individual scores, best-in-class and worst-in-class portfolios are formed of companies for a broad European market index. In a naïve performance analysis, portfolios consisting of the low-rated companies show higher annual returns than the market, whereas high-scoring companies underperform the market. However, when tested in a Fama-French-Carhart four-factor model, evidence is found for positive risk-adjusted excess returns for zero-investment long-short (High-Low) portfolios for the overall environment score and the resource use sub-theme.